Коммуникация в аспекте гендерной лингвистики: женский стиль „стервы” - Татьяна Космеда (Studia Rossica Posnaniensia)
The article elucidates the problem of gender linguistics. The focus is on the feminine linguistics, one of women’s speech styles, so called speech variety – ‘style of the bitch’. The author specifies strategies and tactics of the actualized speech style which are expressed through modelling the speech genre of the praise, speech pattern of the coquette, tactics of the Ego and Alter Ego dialogue, types of verbal play etc. Besides, the semantic structure of the lexeme bitch is outlined to prove that its polysemy reflects enantiosemy and represents intraverbal evaluative antonymy and different stylistic signs resulting from different male and female perception of the world and different types of gender lingual consciousness.